Anmeldelser - Kullberg, Erling (Danish Yearbook of Musicology, 1981)
Review of: Karl Aage Rasmussen: A Ballad of Game and Dream. Svend Nielsen: Kammerkantate. Dansk Musik Antologi 038, Bodil Gümoes, sopran, Tina Wilhelmsen, tale, The Elsinore Players, dirigent Karl Aage Rasmussen. EMl063-39267.